Integrated Flexible Thin Film Sensor Around Angiographic Catheter for Flow Detection. (2017) - Maji, Debashis; Das, Soumen
Abstract: Integration of thin film inorganic sensors over curved surface requires flexibility of the thin film assembly along with the substrate for various applications. In the present study, a micro thin film flow sensor was fabricated over a soft biocompatible PDMS elastomer. A non-planar topology was used for proper orientation of the thin film buckles along the direction of bending along with pre-stretching of the elastomer to account for larger buckles. The resulting sensors demonstrated high flexibility by successfully wrapping around angiographic 2 mm diameter catheter maintaining good electrical continuity. Preliminary flow sensing of a meanderline shaped micro thermal flow sensor was performed using a custom build flow setup for high and low pulsatile flow rates as well as detection of flow abnormalities due to blockage/stenosis formation. The sensors demonstrated significant response to varying degree of blockages at even low flow rates thereby indicating potential application of such sensor for in-vivo catheterial operations.